Hubungan Tingkat Stres dan Kecemasan dengan Kualitas Hidup Pasien Dispepsia Fungsional di Rumah Sakit Umum Kelas D Kabupaten Buol - Abdul Gafur; Bayu Eka Kurniawan; Matius Paundanan (Universitas Widya Nusantara, 2026)
Functional dispepsia is an upper gastrointestinal disorder without any detectable organic abnormalities but often causes chronic symptoms such as epigastric pain, postprandial fullness, and early satiety, which can reduce the patient’s quality of life. Psychological factors such as stres and anxiety are known to play an important role in exacerbating the symptoms of functional dispepsia. This study aimed to analyze the relationship between stres and anxiety levels and the quality of life of patients with functional dispepsia at RSU Kelas D Pratama Buol. The type of research used is quantitative with a cross-sectional design, involving a sample of 53 respondents selected using a purposive sampling technique. Data were collected using standardized questionnaires and analyzed using the Chi-Square test. The results showed that most respondents had a good quality of life (88.68%), while 11.32% had a poor quality of life. There was a significant relationship between the level of stres and anxiety and the quality of life of patients with functional dispepsia at RSU Kelas D Pratama Buol. This study is expected to serve as an additional reference on the relationship between stres, anxiety, and quality of life among patients with functional dyspepsia.